Use of technology in prediabetes and precision prevention - Jie He; Natural Chu; Heng Wan; James Ling; Yincong Xue; Kathy Leung; Aimin Yang; Jie Shen; Elaine Chow (Journal of Diabetes Investigation)
ABSTRACT Controlling the epidemic of diabetes is an urgent global healthcare challenge. The low uptake of diabetes prevention programs highlights difficulties in scalability, partly due to the need for intensive face‐to‐face contact and its impact on healthcare resource utilization. In this narrative review, we will summarize the latest evidence in technology‐assisted lifestyle interventions. We will appraise evidence of digital diabetes prevention programs that use internet platforms or text messaging tools to support information delivery, lifestyle coaching, or peer support. We will also discuss the use of wearables, including physical activity trackers and continuous glucose monitoring (CGM) as part of lifestyle intervention. Experience from diabetes highlights the potential for CGM as a motivational tool to promote lifestyle change. The integration of digital data may facilitate earlier detection of prediabetes, sub‐phenotyping, and personalized nutritional predictions. We will highlight major gaps in research and the need for rigorous clinical trials to evaluate the acceptability and cost‐effectiveness of integrating technologies as part of a multicomponent strategy in diabetes prevention.